Case of limbic encephalitis with anti‐neutral glycosphingolipid antibodies. Issue 2 (4th March 2016) - Takeuchi, Yuko; Ueda, Miki; Ochiai, Jun; Mabuchi, Chiyuki; Shima, Sayuri; Mutoh, Tatsuro
Abstract: We describe a case of a 44‐year‐old man with limbic encephalitis and refractory epileptic seizure. He was found to have developed flaccid paraplegia when he recovered from status epilepticus. Electrophysiological examinations disclosed axonal neuropathy of the lower limbs with nerve roots involvement. Brain fluid‐attenuated inversion recovery‐weighted magnetic resonance imaging showed bilateral medial temporal hyperintensities. Anti‐neutral glycolipid antibodies were detected in the acute phase serum, but disappeared after immunomodulatory therapy. A previous study has shown that anti‐neutral glycolipid antibodies are present in encephalomyeloradiculoneuropathy cases. The present patient initially showed limbic encephalitis phenotype followed by involvement of nerve roots and peripheral nerves, just like in previous encephalomyeloradiculoneuropathy cases. The present case strongly suggests that encephalomyeloradiculoneuropathy might include a phenotype of limbic encephalitis, although we do not have definite grounds for this assumption, which remains to be elucidated. Nevertheless, examination of anti‐neutral glycolipids antibodies is highly recommended for future similar cases.